1999
DOI: 10.2135/cropsci1999.0011183x003900010027x
|View full text |Cite
|
Sign up to set email alerts
|

Rooting, Water Uptake, and Xylem Structure Adaptation to Drought of Two Sorghum Cultivars

Abstract: Several mechanisms have been proposed to explain the high tolerance of sorghum [Sorghum bicolor (L.) Moench] to drought. This paper reports a field study on the effects of soil moisture stress on the rooting habits, transpiration rate, and xylem anatomy of two sorghum cultivars, Tabat (drought susceptible) and Gadambalia (drought tolerant). Two levels of water stress, −0.02 MPa (wet) −0.75 MPa (dry), were applied. Tabat had a higher root length density (RLD), higher late metaxylem (LMX) vessels per nodal root,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
72
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(79 citation statements)
references
References 8 publications
5
72
0
Order By: Relevance
“…hydraulic conductivity (Sperry et al, 2002). Salih et al (1999) reported that Gadambalia took up more water from deep soil layers despite its lower RLD than Tabat. Furthermore, Gadambalia, unlike Tabat, was not affected by drought stress in cross sectional area and capacity of late metaxylem vessels, which implied high hydraulic conductive potential of the nodal roots of Gadambalia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…hydraulic conductivity (Sperry et al, 2002). Salih et al (1999) reported that Gadambalia took up more water from deep soil layers despite its lower RLD than Tabat. Furthermore, Gadambalia, unlike Tabat, was not affected by drought stress in cross sectional area and capacity of late metaxylem vessels, which implied high hydraulic conductive potential of the nodal roots of Gadambalia.…”
Section: Discussionmentioning
confidence: 99%
“…These results indicated that Gadambalia extracted more water, especially from deep soil, under drought stress. Salih et al (1999) reported that Gadambalia had higher effi ciency in extracting soil water from 0-0.9 m depth than Tabat although Gadambalia had a lower RLD. The present study indicated that Gadambalia extracted more water than Tabat from deeper soil layers (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basal stem diameter at 50 DAS was 14.5 mm in the dry season and 74.5% of that in the rainy season. Salih et al (1999) conducted fi eld tests of sweet sorghum with irrigation totaling 700 mm and 300 mm by 50 mm in 5-day and 12-day intervals; they reported morphological differences in vascular bundles, etc. The total precipitation during the growth period of this experiment was 260 mm in the dry season and 1,190 mm in the rainy season, suggesting that different interior morphological characteristics were discernible between the two conditions.…”
Section: Climate and Growthmentioning
confidence: 99%
“…The sweet sorghum stems, containing high concentrations of sugar, are the most important product for use as a raw material for fermentation in MSG factories. Considering the operating effi ciency of MSG factories, sweet sorghum would ideally be harvestable throughout the year, but it was reported that stem length and stem diameter are affected by the amount of irrigation (Salih et al, 1999). The sweet sorghum stem consists of internodes, similarly to other gramineous crops.…”
mentioning
confidence: 99%